A map describing routes used in goose monitoring at Meise Botanic Garden - Groom, Quentin (Zenodo, 2019)
The geese living in Meise Botanic Garden were surveyed between October 11, 2011 - July 10, 2017. Each day that the geese were monitored one route was chosen at random. This map describes those routes routemap.png A map of the survey routes within the Botanic Garden. CC BY-SA The background map is derived from the OpenStreetMap see https://www.openstreetmap.org/copyright